Improving Business Model for Composter Business: Case Study of PASMA (Journal of Innovation, Business and Entrepreneurship, 2020)
PASMA, a waste processing company based in Bandung offers people a convenient way of composting through their composter device, however, they faced an issue of customer irrelevant in buying the composter device. To analyze this problem, certain analysis such as Porter's Five Forces, PESTLE, stakeholder analysis, market analysis, business model analysis, and internal situation analysis is conducted. The result shows that PASMA stagnant in sales are caused by PASMA's primary constraints in lack of marketing effort in funnelling and awareness, limited capital in finance, challenges in adjusting the technology cost, and lack of knowledge from the human resources. Several solutions were proposed in order to improve the sales activity as well as the managerial performance of PASMA, such as improving financial planning and create a strict budget allocation, improving the marketing strategy such as developing new channels and revenue streams as well as improving customer relationship through online presence and hospitality service, building collaboration with expertise and focusing to sell simpler compost bin may improve the cash flow of PASMA, and lastly, maintaining and managing internal and external management and relationship by setting and tracking goals for each department. The result of this study could help other businesses to improve and strengthen their business model value creation for composter products in Indonesia, under the condition that since the compost industry is still growing throughout the year, further study about the recent compost industry is recommended.Keywords: Leadership, Leadership Style, Organization, Employee Performance, Z generation